2020
DOI: 10.7759/cureus.11828
|View full text |Cite
|
Sign up to set email alerts
|

“Near-Miss” Obstetric Events and Maternal Deaths in a Rural Tertiary Care Center in North India

Abstract: Introduction Maternal near-miss and maternal mortality cases have common characters, especially in terms of risk factors. Both of them are indicators of the quality of health care services provided to pregnant women. Our center is a tertiary care center in a rural area of western Uttar Pradesh (U.P.) so we get a large number of referred cases from most of the rural areas of western U.P. and the adjoining areas of other states too, which sometimes end up in mortality. Thus this study was planned to find out the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Both MNMR and SMOR give an estimate of the amount of care and resources that would be needed to improve obstetric care in that area or facility. We reviewed studies done in different parts of India, and the near-miss ratio ranged from 120 to 10.4 ( Table 12) [10][11][12][13][14][15][16][17][18][19][20][21][22]. However, all these studies have used different criteria in identifying near-miss cases and hence technically not ideal for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Both MNMR and SMOR give an estimate of the amount of care and resources that would be needed to improve obstetric care in that area or facility. We reviewed studies done in different parts of India, and the near-miss ratio ranged from 120 to 10.4 ( Table 12) [10][11][12][13][14][15][16][17][18][19][20][21][22]. However, all these studies have used different criteria in identifying near-miss cases and hence technically not ideal for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…10 Studies from Karachi and neighbouring country India showed maternal near-miss rate was around 16.6 to 31.4 per 1000 live births. 14,15 Multiple factors may be responsible for these increased figures, including hospital setting and geographical location.…”
Section: Discussionmentioning
confidence: 99%